Strengthening Pathology Capacity to Deliver Quality Cancer Care in Cities in LMICs. (2021) - Frech, Silvina; Bravo, Luis Eduardo; Rodriguez, Ingrid; Pomata, Alicia; Aung, Khin Thida; Soe, Aung Naing; Hornburg, Beatriz; Guarner, Jeannette; Brock, Jane; Camacho, Rolando; Milner, Dan
Abstract : Diagnostic pathology services for oncology health systems are essential; yet, surveys, observations, and hard data from across low- and middle-income countries have revealed that these services are almost always lacking adequate quality and often missing completely. The City Cancer Challenge Foundation (C/Can), the American Society for Clinical Pathology, and C/Can partner cities undertook intense analysis of their existing pathology services as part of a year-long assessment process including the specific formation of a pathology-focused team. Internal and external expert assessments identified sustainable solutions adapted to the local context and level of resources and created specific local implementation projects. Through local leadership, capacity development, and collaboration, services were improved city-wide in three cities: Cali, Colombia; Asunción, Paraguay; and Yangon, Myanmar. Common problems identified across cities included deficiencies in personnel training, equipment, reagents, processes, quality, and coordination. Specific solutions included quality training, standard process development and regulation, implementation of new services, and public-private collaboration. As the first cities joining the C/Can initiative, Cali, Asunción, and Yangon demonstrate the success of the approach and the value of local expertise in identifying problems and solutions. The additional value of international partners' expertise created opportunities for growth through mentorship and technical support. Importantly, the power of healthcare programs with strong political support is emphasized.